2017
DOI: 10.12688/f1000research.11118.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in managing gastrointestinal stromal tumor

Abstract: Constitutive activating mutations in KIT and platelet-derived growth factor receptor α ( PDGFRα) are heavily involved in the pathobiology of gastrointestinal stromal tumors (GISTs). This disease has served as an effective “proof-of-concept” model for targeting gain-of-function kinase mutations in cancer. This review discusses the current standard of care in terms of pharmacotherapy in the management of localized and metastatic GISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Drug resistance and tumor recurrence are most of the concerns in clinical practices of GIST . To deal with these, our study has revealed a novel tumor promoter, DKK4, which was upregulated by activated Wnt pathway in high‐risk GIST, promoting tumor progression via forming the immune suppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug resistance and tumor recurrence are most of the concerns in clinical practices of GIST . To deal with these, our study has revealed a novel tumor promoter, DKK4, which was upregulated by activated Wnt pathway in high‐risk GIST, promoting tumor progression via forming the immune suppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance and tumor recurrence are most of the concerns in clinical practices of GIST. 42,43 To deal with these, our study has revealed a novel tumor promoter, DKK4, which was upregulated by activated Wnt pathway in high-risk GIST, promoting tumor progression via forming the immune suppressive microenvironment. Owing to necessity of immune cells participation in drug effects, DKK4 partially accounts for the weak sensitivity to RTK inhibitor in some cases, and can be recognized as a therapeutic target to enhance drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of GISTs (gastrointestinal stromal tumours) possess mutually exclusive mutations in platelet‐derived growth factor subunit A (PDGFRA) or KIT, which constitutively activate the encoded receptor tyrosine kinases (RTKs) to control the response to imatinib treatment and lead to tumorigenesis . In adults, 10%‐15% of GISTs exhibit wild‐type KIT and PDGFA genes but may bear mutated neurofibromatosis type 1 (NF1), BRAF, or succinate dehydrogenase (SDH) genes . Both the NIH (Bethesda, MD) and National Comprehensive Cancer Network (NCCN) schemes are deemed effective for risk stratification in GIST, whereas their prognostic utility is not uniformly validated, and the NCCN scheme lacks sufficient evidence‐based data for some uncommon settings .…”
Section: Introductionmentioning
confidence: 99%
“…neurofibromatosis type 1 (NF1), BRAF, or succinate dehydrogenase (SDH) genes. 3,4 Both the NIH (Bethesda, MD) and National Comprehensive Cancer Network (NCCN) schemes are deemed effective for risk stratification in GIST, whereas their prognostic utility is not uniformly validated, and the NCCN scheme lacks sufficient evidence-based data for some uncommon settings. 5,6 Another challenge in the current care of GIST patients is the inevitable resistance to imatinib that emerges following initial responses due to acquired secondary mutations.…”
mentioning
confidence: 99%
“…However, other mutations may be present in these tumors, with the largest group represented by succinate dehydrogenase-deficient GIST by immunochemistry, which may reflect underlying alterations in an succinate dehydrogenase subunit, and may be associated with familial heritable syndromes (Carney triad or Carney-Stratakis syndrome) [10][11][12][13][14]. Other subtypes of GIST lacking activating mutations in KIT or PDGFRA may have mutations in NF1 (usually associated with neurofibromatosis type 1) or in BRAF or KRAS [15][16][17]. Very recently, cases of GIST-like tumors harboring NTRK translocations have further expanded the spectrum of molecular subtypes [18].…”
Section: Disease Overviewmentioning
confidence: 99%